Information flow and the adoption of soil-improvingand water conservation measures, and householdwelfare: Insights from a randomized controlled trialin Uganda - Mbabazi, Gloria Esther; Awudu Abdulai; Kikulwe, Enoch; Gotor, Elisabetta (Wiley, 2025)
Extension services are designed to facilitate the flow of information from researchers to farmers. However, information failures continue to impede the diffusion of soilimproving and water conservation technologies in Sub-Saharan African countries. We use a randomized controlled trial (RCT) to examine the impact of an extension-based campaign on the adoption of soil and water conservation measures and welfare outcomes among farmers in Uganda. The experiment involves the use of mass media including radio programs and video shows, lecture trainings, and practical sessions involving demonstration trials and farmer field days in disseminating information pertinent to soil-improving and water conservation practices. We compare the impact of utilizing audio-visual and hands-on approaches in disseminating information relative to audio means of communication. We employ machine learning techniques to analyze the heterogeneous effects and for covariate adjustment. We find that augmenting mass media in public extension has far-reaching effects. Our results reveal that the transmission of information through multiple communication channels significantly increases the adoption of the soil-improving and water conservation measures. We also find that the intervention significantly increases welfare measures like banana yields, marketed surplus, and household incomes. These findings provide evidence that the use of mass media for increased awareness of improved technologies and utilizing audio-visual and hands-on communication channels in facilitating changes in attitudes and behavior of the end-users, can enhance the adoption of these technologies and contribute to increased household welfare.